The impact of strategy, environment, and the management system on the foreign subsidiary: The implication for open innovation - Margarida Rodrigues; Maria do Céu Alves; Cidália Oliveira; José Vale; Rui Silva (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
With globalisation, there has been an intensification of investments by foreign groups in sectors strategic to their country of origin, such as some minerals. It is, therefore, crucial for a parent company to implement specific controls in its management control systems. In these circumstances, this study aims to determine the degree of control exercised by the parent company over a subsidiary in cultural and organisational dimensions. In addition, other exogenous factors (entities and external factors) influence this system. The results obtained showed that the parent company had an influence on the Management Control System (MCS) of the subsidiary and changed the way control was exercised there, but was unable to deal with macroeconomic instability, environmental and strategic uncertainty, and, consequently, the management risk involved in the extractive activity; in this case, for this subsidiary to operate a seam mine and not be aware of it since it is essentially a commercial, economic group. In addition to these effects on the organisational dimension and the cultural dimension, the shareholders were unable to integrate the subsidiary's organisational and local culture, which generated some dynamic tension with the expatriate. In addition to the theoretical framework used, it was confirmed that the Flamholtz model is passive to implement in industries in general, particularly in the extractive industry. Finally, some final considerations were made about the management control system, in which the argument is reinforced that there must be empathy between the local staff and the expatriate, as a representative of the shareholders, in order for this system to be a vehicle for the effective transfer of knowledge between both parties, as well as to be supported by open innovation.
Keywords: 650; multinational; subsidiary; strategy; institutional environment; management control system